Penggunaan metode mind mapping dalam keterampilan menulis teks eksplanasi di SD - Siti Megayati; Indihadi, Dian; Saputra, Erwin Rahayu (IKIP Siliwangi, 2024)
Writing is an activity that can explore one's thoughts and feelings about an object, choose what to write and write it down so that the reader will understand clearly. Writing can be said as one of the 4 aspects of language including listening, speaking, reading, and writing. According to Susanto (2013: 241) stated, language skills performed by humans in the form of listening, speaking, reading, and writing are capitalized by vocabulary, namely intellectual activity, the work of an educated human brain. Writing is the skill of a person (individual) communicating messages in a piece of writing. In accordance with the opinion of Susanto (2013: 248) stated